Tafolecimab, a novel potential long-acting PCSK9 monoclonal antibody: efficacy and safety in healthy and hypercholesterolemia subjects. (25th November 2020) - Cui, Y; Huo, Y; Li, X; Yang, G; Huang, Z; Zhao, X; Qi, L; Deng, H; Zheng, S; An, P; Sun, X; Li, H; et al.
Abstract: Background: LDL cholesterol (LDL-C) is a well-established risk factor for cardiovascular disease. PCSK9 binds LDL receptors, targeting them for degradation. The dosing intervals for currently available PCSK9 monoclonal antibodies are once every 2 or 4 weeks. Tafolecimab, a novel recombinant human PCSK9 monoclonal antibody, was found to have higher affinity with PCSK9 and show longer LDL-C reduction compared to evolocumab in preclinical studies. Purposes: The objectives for the SAD and MAD studies were to investigate the safety and efficacy of tafolecimab and explore the optimal dosing schedule. Methods: The phase 1 study was a randomized, placebo-controlled, double-blind, single-ascending dose study (SAD) in Chinese healthy subjects, who were randomized 3:1 to tafolecimab and placebo (n=58). SAD subjects received tafolecimab subcutaneously at 25/75/150/300/450/600mg, or intravenously at 75/450mg, monitored up to day 84. The phase 2 study was a randomized, double-blind, placebo-controlled, repeated-dosing, multiple ascending dose (MAD) study in patients with hypercholesterolemia, who were randomized 4:1 to tafolecimab and placebo (n=60). MAD subjects received tafolecimab subcutaneously at 75/140mg every 2 weeks, 300/420mg every 4weeks, 450/600mg every 6 weeks up to day 84 or 98 with 3 months follow-up. Results: In the SAD, the maximum mean reduction in LDL-C ranged from 52.2% to 72.1% and was achieved as early as 5 days (figure 1a). The duration of LDL-C reduction was tafolecimab dose dependent. In the MAD, the mean LDL-C concentrations were reduced by tafolecimab for each dose at 12 weeks relative to baseline (ranging from 54.30% to 72.26%; p<0.001). Particularly, a 56.52% (−72.50%, −40.54%) reduction of LDL-C was observed in the cohort of 600mg Q6W. The effect sustained till week 14 (8 weeks after the last dose) where there was still a 43.46% (−60.96%, −25.96%) reduction from baseline (figure 1b). The mean reduction of Lp(a) at week 12 ranged from 24.04% to 50.59% relative to baseline. Tafolecimab reduced the other lipids when comparing with placebo. The pharmacokinetics/pharmadynamics (LDL-C) profiles of tafolecimab were well characterised and support the potential dosing interval of 6–8 weeks subcutaneously. Both healthy and hypercholesterolemia subjects are generally tolerable to tafolecimab. Reported treatment-emergent adverse events (TEAEs) were: tafolecimab 23 (52.3%) vs. placebo 8 (57.1%); tafolecimab 34 (70.8%) vs. placebo 9 (75.0%) in the SAD and MAD respectively. There were no serious TEAEs or events leading to death or treatment discontinuation in both SAD and MAD. Conclusions: Tafolecimab was well tolerated in both healthy and hypercholesterolemia in Chinese subjects, and improved lipid profile including LDL-C, Lp(a) and other lipids. The sustained effects on LDL-C suggests the potential of tafolecimab as a long-lasting PCSK9 inhibitor with dosing interval of 6–8 weeks or beyond. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Innovent Biologics (Suzhou), China